Pengembangan Usaha Jamur Tiram Untuk Meningkatkan Perekonomian (Studi Kasus Pada Kelompok Petani Jamur Tiram Manut Di Kecamatan Klakah Kabupaten Lumajang) - Al Sabet, Fia Birtha (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
The UMKM sector is a pillar of the National Economy which has a strategic role in supporting the people's economy, including in terms of equal distribution of income, absorption of the workforce, as well as the social and economic environment of the community. KPJT Manut is an oyster mushroom farming group located in Klakah Village, Klakah subdistrict, Lumajang district. who cultivate many horticultural crops, including vegetables, which are becoming a superior product among farmers in the hope of increasing income on an economic scale and living a more prosperous life. The focus of the problem in this research is what is the strategy for developing the oyster mushroom business at KPJT Manut to improve the community's economy and what are the supporting and inhibiting factors in implementing the oyster mushroom business development strategy at KPJT MANUT. The purpose of this research is to determine the strategy for developing the oyster mushroom business at KPJT Manut in order to improve the community's economy, and to determine several supporting and inhibiting factors in implementing the oyster mushroom business development strategy at KPJT MANUT. This research uses a qualitative method with a case study approach. The data collection method used was observation, interviews, documentation, and the analytical processing technique used was descriptive qualitative. The results of this research conclude: the business development strategy carried out by KPJT Manut is to increase the number of special membership for oyster mushroom farmers, increase innovation and creativity of members, and socialization and guidance programs while the inhibiting factor in the oyster mushroom business development strategy at KPJT Manut is business capital.